"I have an idea!": A disabled refugee's curriculum of navigation for resettlement policy and practice. Issue 3 (26th May 2020) - Bonet, Sally Wesley; Taylor, Ashley
Abstract: Disabled refugees experience multiple barriers through the process of resettlement, and yet, their perspectives are rarely solicited in discussions of refugee policy and practice. This article focuses on the life history and resettlement experiences of Samir Omar, a disabled refugee, who recounts how he learned to navigate resettlement through his interactions with the state. Data for this article comes from a three year, multisited, multilingual ethnography conducted with refugee families who have been recently resettled to the United States. This larger study, in which Samir was a participant, examined the ways refugees' encounters with the state come to bear on their embodiments and understandings of citizenship. Leveraging a critical disability studies theoretical lens, we analyze the production of Samir's disability through displacement and resettlement, as well as the framing of his disability as barring him from productive citizenship. We argue that the refugee resettlement process is inherently educative, resulting in Samir's sustained critique of the able-bodied norms of citizenship. Samir produces his own "curriculum of navigation" for disabled refugees that offers an alternative policy for resettlement and reframes able-bodied notions of dependency and self-sufficiency.